La coordinación general en la enseñanza aprendizaje de los fundamentos técnicos del baloncesto en niños de 11-12 años de la Liga Deportiva Cantonal de Saraguro de la provincia de Loja en el período 2014-2015 - Ordóñez Macas, Mayra Liliana (2016)
This research entitled: THE GENERAL COORDINATION IN LEARNING TEACHING OF TECHNICAL FUNDAMENTALS OF BASKETBALL IN CHILDREN 11-12 years LEAGUE SPORTS SARAGURO Cantonal PROVINCE IN LOJA 2014-2015. The central issue before us is what methodological coordinative exercises can enhance the learning of the technical fundamentals of basketball in children aged 11-12 years, Liga Deportiva Cantonal de Saraguro Loja Province?. Our overall objective is framed determine an exercise program and methodological development games to improve overall coordination of the technical fundamentals of basketball in children 11-12 years of Liga Deportiva Cantonal de Saraguro in the province of Loja in the period 2014 -2015. The methods used in this research were: Scientific Method, Deductive and inductive statistical method. They allowed us to guide and direct the research process, in which a sample of 20 children aged 11-12 years and 4 coaches which were given a survey and pre-test and post-test athletes took investigated . The most important research results were that 75% of coaches were trained to provide a better learning of general coordination with the various technical fundamentals of basketball. 90% of athletes improved what is the overall coordination with the various technical fundamentals of basketball with the proposed methodological exercises. And in conclusion we propose an alternative: Program exercises and games to improve methodological development of the overall coordination of the technical fundamentals of basketball, to give solution to the problem.